Secondary Education and the Raising of the School-Leaving Age Coming of Age? - Woodin, Tom.; McCulloch, Gary.; Cowan, Steven; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
The progressive raising of the school-leaving age has had momentous repercussions for our understanding of childhood and youth, for secondary education, and for social and educational inequality. This book assesses secondary education and the raising of the school-leaving age in the UK and places issues and debates in an international context.
Keywords: Education; History, Modern; Great Britain -- History; International education; Comparative education; Educational policy; ducation and state; Education -- History; Education and state; Education; Educational Policy and Politics; International and Comparative Education; Education Policy; History of Britain and Ireland; History of Education; Modern History